1.55 µm emission from a single III-nitride top-down and site-controlled nanowire quantum disk. (5th July 2017) - Chen, Qiming; Yan, Changling; Qu, Yi
Abstract: InN/InGaN single quantum well (SQW) was fabricated on 100 nm GaN buffer layer which was deposited on GaN template by plasma assisted molecular beam epitaxy (PA-MBE). The In composition and the surface morphology were measured by x-ray diffusion (XRD) and atom force microscope (AFM), respectively. Afterwards, the sample was fabricated into site-controlled nanowires arrays by hot-embossing nano-imprint lithography (HE-NIL) and ultraviolet nanoimprint lithography (UV-NIL). The nanowires were uniform along the c -axis and aligned periodically as presented by scanning electron microscope (SEM). The single nanowire showed disk-in-a-wire structure by high angle annular dark field (HAADF) and an In-rich or Ga deficient region was observed by energy dispersive x-ray spectrum (EDXS). The optical properties of the SQW film and single nanowire were measured using micro photoluminescence ( µ -PL) spectroscopy. The stimulating light wavelength was 632.8 nm which was emitted from a He-Ne laser and the detector was a liquid nitrogen cooled InGaAs detector. A blue peak shift from the film material to the nanowire was observed. This was due to the quantum confinement Stark Effect. More importantly, the 1.55 µ m emission was given from the single disk-in-a-wire structure at room temperature. We believe the arrays of such nanowires may be useful for quantum communication in the future.